1998
DOI: 10.1037/0735-7036.112.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Pavlovian conditioning of social affirmative behavior in the Mongolian gerbil (Meriones unguiculatus).

Abstract: Gerbils learned to approach a spatial-olfactory stimulus that signaled access to their pairmate. Experiments 1 and 3 used a discrimination procedure in which 1 conditioned stimulus (the CS+) was presented immediately before access to the pairmate and another (the CS-) was presented alone. Both male and female gerbils came to approach the CS+ sooner than the CS- and spent more time near the CS+ than the CS-. Discrimination learning was facilitated by making the CS+ and CS- spatially distinct (Experiment 3). Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…In particular, the presence of a reward system allows an individual to reinforce actions increasing satisfaction and material rewards and thereby adjust behavior by learning to produce goal-oriented action paths (Thorndike, 1911;Herrnstein, 1970;Sutton and Barto, 1998;Niv, 2009). It is probable that behaviors as different as foraging, mating, fighting, cooperating, nest building, or information gathering all involve adjustment of actions to novel environmental conditions by learning, as they have evolved to be performed under various ecological contexts and with different interaction partners (Hollis et al, 1995;Chalmeau, 1994;Villarreal and Domjan, 1998;Walsh et al, 2011;Plotnik et al, 2011). * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the presence of a reward system allows an individual to reinforce actions increasing satisfaction and material rewards and thereby adjust behavior by learning to produce goal-oriented action paths (Thorndike, 1911;Herrnstein, 1970;Sutton and Barto, 1998;Niv, 2009). It is probable that behaviors as different as foraging, mating, fighting, cooperating, nest building, or information gathering all involve adjustment of actions to novel environmental conditions by learning, as they have evolved to be performed under various ecological contexts and with different interaction partners (Hollis et al, 1995;Chalmeau, 1994;Villarreal and Domjan, 1998;Walsh et al, 2011;Plotnik et al, 2011). * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…First, varying environments need to be considered because learning is favored by selection when the environment faced by the individuals in a population is not absolutely fixed across and/or within generations (Boyd and Richerson, 1985;Rogers, 1988;Stephens, 1991;Feldman et al, 1996;Wakano et al, 2004;Dunlap and Stephens, 2009). Second, frequencydependence needs to be considered because learning is likely to occur in situations where there are social interactions between the individuals in the population (Chalmeau, 1994;Hollis et al, 1995;Villarreal and Domjan, 1998;Giraldeau and Caraco, 2000;Arbilly et al, 2010Arbilly et al, , 2011bPlotnik et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hollis et al (1989) observed conditioned frontal displays in both male and female gourami. In contrast to this result, both female and male Mongolian gerbils have been found to approach and remain near a sexually condi-tioned olfactory/spatial CS (Villarreal & Domjan 1997). In studies with Japanese quail, Gutiérrez and Domjan (1997) found that females are much less likely than males to approach and remain near a CS that is paired with the presentation of a sexual partner.…”
Section: Sexual Conditioning Of Femalesmentioning
confidence: 91%
“…The CS was paired with access to the subject's pair-mate during the postpartum estrus period of the female (Villarreal & Domjan 1997). In these studies a compound olfactory/spatial cue served as the CS.…”
Section: Sexual Conditioning In Small Mammalsmentioning
confidence: 99%
See 1 more Smart Citation